STRATEGIC CONVERGENCE OF EAST AND WEST: U.S. AND CHINA’S MILITARY DOCTRINES IN THE AGE OF ARTIFICIAL INTELLIGENCE - Anak Aman, Herlin; Roslam, Aini Fatihah; Krisnan, Tharishini (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The relationship between the United States and China has evolved through multiple phases since the Cold War era—shifting from ideological confrontation to diplomatic engagement and now entering a phase of strategic technological rivalry. Within this context, the rise of artificial intelligence (AI) has reshaped the global security landscape and challenged traditional frameworks of military planning and doctrine. This study analyzes the convergence and adaptation of military doctrines between the world’s two major powers—the United States and China—considering rapidly evolving AI technologies. Through a comparative analytical approach, the paper examines how both nations conceptualize and implement AI within their military strategies, particularly in intelligence operations, autonomous weapons systems, and cyber warfare capabilities. The study also explores how differing strategic cultures between East and West influence defense policymaking and the application of AI in military affairs. Findings indicate that, despite divergent values and philosophies, both countries are moving toward strategic convergence in shaping future military paradigms centered on technological innovation. These insights are crucial for understanding great power dynamics in an era of intensifying technological competition and their broader implications for global security.